Russian Higher Education in Conditions of Professional Standardization: Experience, Challenges, Risks - E. G. Elina; E. N. Kovtun; S. E. Rodionova (Moscow Polytechnic University, 2019)
The authors of the article are the experts of Federal Educational and Methodological Union (FEMU) in the training direction "Linguistics and Literature", who have worked out three subsequent versions of State Educational Standards, including the last version of Federal State Educational Standard (FSES 3++) and Samples of Basic Educational Programs (SBEP) in the training direction of higher education (HE) "Philology". The given article provides an overview of the main stages of Russian education standardization within the period of 1990-2010 and its further adaptation to the market requirements. The experts focus their attention on the problems of working out and implementing since 2012 the Professional Standards essential for carrying out different kinds of professional activities.The given investigation summarizes the problems discussed in substantive methodological literature that the Russian higher education has to deal with in the conditions of professional standardization. The authors of the article analyze in detail the experience of the FEMU with the view to display the variety of approaches suggested by the authors of FSES HE in correlation with professional standards - from the broadest approach implying the conformity of FSES HE with dozens of professional standards to the narrowest trend designating that a graduate student's professional activity is only restricted to scientific and pedagogical spheres. Consequently, there is a threat that the variety of approaches may cause in future certain difficulties in coordinating the educational processes in higher educational institutions and in case of uncontrolled extrapolation may result in the downfall of the unified Russian educational system.In the concluding part of the investigation the authors share their know-how in correlating the Educational Standards in "Philology" (HE) with professional standards, dwell on their positive experience of aligning the competence model of the graduate student in FSES and SBEP with the norms of professional standards.